Beyond Being There: The Symbolic Role of Communication and Identification in Perceptions of Proximity to Geographically Dispersed Colleagues1 - O’Leary, Michael Boyer; Wilson, Jeanne M.; Metiu, Anca (MIS Quarterly, 2014)
Using a mixed-methods approach, we develop the concept of perceived proximity, which is created through communication, shared identity, and the symbolic aspects thereof. Building on previous theoretical work, we create and validate measures of perceived proximity. Then, we compare how perceived proximity and objective distance relate to relationship quality for collocated and geographically dispersed work colleagues. Our results show that perceived proximity (i.e., a cognitive and affective sense of relational closeness) and not physical proximity (i.e., geographic closeness measured in miles or kilometers) affects relationship quality in an international survey of more than 600 people and 1,300 dyadic work relationships. We also find that people’s perceptions of proximity mediate the effects of communication and identification on relationship quality. Using qualitative data (2,289 comments from 1,188 respondents coded into 9 themes), we explore the symbolic meaning of perceived proximity. We show how people can form strong bonds despite being separated by large distances and continue to shift the emphasis from information systems as “pipes” or channels to information systems as vehicles for conveying shared meaning and symbolic value. Our findings have important implications for scholars, managers, systems designers, and members of virtual teams, teleworkers, and other geographically dispersed contexts.